2019
DOI: 10.1021/acsabm.8b00833
|View full text |Cite
|
Sign up to set email alerts
|

Microgrooves Encourage Endothelial Cell Adhesion and Organization on Shape-Memory Polymer Surfaces

Abstract: Cardiovascular stents have become the mainstay for treating coronary and other vascular diseases; however, the need for long-term anti-platelet therapies continues to drive research on novel materials and strategies to promote in situ endothelialization of these devices, which should decrease local thrombotic response. Shape-memory polymers (SMPs) have shown promise as polymer stents due to their self-deployment capabilities and vascular biocompatibility. We previously demonstrated isotropic endothelial cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Literature shows a large variety of ranges and architectures affecting the EC alignment. ECs have been aligned by using: nanofibrils made of 30-50 nm collagen I fibers [13]; micropatterns mostly made of fibronectin with 2.5 μm-100 μm stripes [14,15,16]; microgrooves with ridges and grooves ranging from 200 nm to 10 μm and depths of 50 nm to 5 μm [17,18,19,20,21]; and fewer topographies with sinusoidal features with 20 μm wavelength and 6.6 μm amplitude [22]. Previously, we have shown that directional gradients can be used for screening the morphological and phenotypical response of osteoblasts [23,24], adipose tissue-derived stromal cells (ASCs) [25], and myoblasts [26].…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows a large variety of ranges and architectures affecting the EC alignment. ECs have been aligned by using: nanofibrils made of 30-50 nm collagen I fibers [13]; micropatterns mostly made of fibronectin with 2.5 μm-100 μm stripes [14,15,16]; microgrooves with ridges and grooves ranging from 200 nm to 10 μm and depths of 50 nm to 5 μm [17,18,19,20,21]; and fewer topographies with sinusoidal features with 20 μm wavelength and 6.6 μm amplitude [22]. Previously, we have shown that directional gradients can be used for screening the morphological and phenotypical response of osteoblasts [23,24], adipose tissue-derived stromal cells (ASCs) [25], and myoblasts [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microgrooves are widely used for cell research. [ 58–61 ] Besides, scientists have investigated dynamic wettability [ 62 ] and microoptical devices [ 63 ] on SMP microgrooves.…”
Section: Development Of Smp Micro/nanopatternsmentioning
confidence: 99%
“…Therefore, microgrooves are widely used for cell research. [58][59][60][61] Besides, scientists have investigated dynamic wettability [62] and microoptical devices [63] on SMP microgrooves. In order to explore the impact of topographic transitions on cells, Davis et al [64] first proposed a thermally responsive cell culture system based on SMP microgrooves.…”
Section: Microgroovesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 174 ] Similar results were discovered on polyurethane‐based shape memory polymers (SMPs) where microgrooves were found to increase surface hydrophobicity which helped to align endothelial cells along the microchannels. [ 175 ] PIII is another surface modification technique where ion‐induced carbonization and oxidation helps to covalently immobilize biomolecules to the surface. [ 176 ] PIII applied to polyurethane enhanced surface wettability and promoted saturation of collagen attachment.…”
Section: Bare or Surface‐modified Stentsmentioning
confidence: 99%